Efek penggunaan LKS IPA tema pemenfaatan tekanan mengintegrasikan literasi saintifik pada kompetensi siswa kelas VIII SMPN 31 Padang - Kitty Mulyati Chania; Asrizal A; Yulkifli Y; Renol Afrizon (Universitas Negeri Padang, 2019)
The 21st century is known as the knowledge era. This era challenges students have various abilities. The government has answered this challenge by improving the quality of education through revising the 2006 curriculum become the 2013 curriculum. In the 2013 curriculum was applied integrated science teaching to improve competence of students. Another government effort was to encourage the school literacy program. But the real condition of the schools showed that knowledge aspect of students was still quite sufficient. One solution to solve this problem was to apply of integrated science worksheet by integrating the scientific literacy in teaching. The purpose of this research was to investigate the effects of the application of science student worksheet on the theme of the use of pressure by integrating scientific literacy on the competencies of grade VIII students in SMPN 31 Padang. The type of research which used was a quasi-experimental design with group Randomized Posttest-Only Control Grup Design. The sampling technique which used was purposive sampling and cluster random sampling. The population of this research was all grade VIII students of SMPN 31 Padang. The sample class consists of two classes, namely the experimental class and the control class. Class VIII.3 was used as the experimental class and class VIII.4 was used as the control class. The instruments which used in the data collection were written test sheet for knowledge aspect, observation sheet for attitude aspect, and performance assessment sheet for the skills aspect of competencies. The research data were analyzed by using descriptive statistics and a comparison of two means test. The result of hypothesis testing indicated that there was a significant difference between the competencies of students who use integrated science student worksheet with students didn’t use it. The result of this test indicated that integrated science worksheet has a significant effect on competencies of students, including aspects of knowledge, skills, attitudes on grade VIII in SMPN 31 Padang with 95% confidence level. Therefore, integrated science worksheet by integrating scientific literacy can be implemented for science teachers and students in science teaching.